Effective stakeholder engagement in integrated river basin management within the context of water resources in Malaysia - Lim, Chow Hock (2025)
Integrated River Basin Management (IRBM) has become increasingly vital in addressing the complex issues surrounding global water resources management, with stakeholder engagement recognised as one of the crucial elements for IRBM. This study aims to develop a comprehensive conceptual framework for stakeholder engagement tailored to Malaysia’s IRBM context, ensuring more effective collaboration in addressing water resource issues. It seeks to identify gaps in existing stakeholder engagement frameworks and examines their perspectives on IRBM to determine key factors that influence effective engagement. This study determined the type and mechanism of stakeholder engagement, identified key stakeholders and selection criteria, examined the factors that contribute to effective engagement from individual stakeholder perspectives, and analysed organisational roles and perspectives that contribute to effective stakeholder engagement. The research hypothesis suggested that inclusiveness, engagement strategies, stakeholder characteristics, organisational factors, and cultural and religious aspects influence stakeholder engagement effectiveness in IRBM. A mixed-method experimental design is adopted, combining quantitative survey data and qualitative interview insights to provide a holistic understanding of stakeholder engagement dynamics. It highlights the importance of inclusive engagement, selection criteria, information access, local knowledge integration, and navigating diverse interests for fostering collaborative solutions. These engagement methods prioritise effective leadership in water management, as well as the establishment of monitoring and evaluation tools. The findings from the surveys identified a spectrum of factors affecting the effectiveness of stakeholder engagement across three stages of the engagement process: pre-engagement, during-engagement, and post-engagement. The response from the interviews not only validated most of the surveys’ findings but also provided further insights, such as the need for adequate financial resources and the caution on involving politicians during the engagement processes. A robust conceptual framework is developed, outlining five independent variables crucial for successful stakeholder engagement: inclusiveness, engagement strategies, stakeholder characteristics, organisational factors, and cultural and religious aspects. Unlike existing IRBM engagement models, this framework integrates cultural, religious, and governance factors tailored to Malaysia’s socio-political landscape. The effectiveness of engagement is determined by three dependent variables: knowledge transfer, decision impact, and stakeholder satisfaction; enhanced by adopting multi-stakeholder platforms (MSP), the Environmental, Social, and Governance (ESG) principles, and the whole-of-government and society (WGS) approaches. Major findings reveal that stakeholder engagement effectiveness is significantly enhanced when cultural and religious considerations are incorporated alongside governance-driven strategies. The study highlights the urgent need for an improved stakeholder engagement framework in Malaysia to address water issues and challenges. It provides a structured approach to refining IRBM policies, equipping policymakers with strategies for more inclusive, transparent, and multidisciplinary participation. By fostering collaborative problem-solving, this study also establishes a foundational reference for future IRBM policy development and research.